PHYSICAL LITERACY LEVEL IN EARLY CHILDHOOD: USING THE PL-C QUEST INSTRUMENT - Friskawati, Gita Febria (Universitas Muhammadiyah Kuningan, 2024)
The physical literacy level of early childhood must be known to determine appropriate intervention in the future. This research will reveal the level of physical literacy of young children using a survey method. A total of 105 children were involved in this research from various types of formal and non-formal early childhood education services. Sampling used convenience sampling to maintain the code of ethics for research in early childhood. The PL-C Quest instrument is used to measure the physical literacy level of early childhood. The data is processed descriptively, then categorization is made for the measurement results. The results reveal that the physical literacy level of boys is the highest compared to girls. The level of physical literacy in all domains for boys is in the medium category, while in the physical and psychological domains for girls is in the low category and the social and cognitive domains are in the medium category. These results can be used as a basis for creating intervention programs to increase physical literacy in early childhood education.